PUSAT TERAPI ANAK DOWN SINDROM DI BANJARMASIN - Parore, Melina Westy; Rahman, Akbar (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
The Down syndrome Children's Therapy Center in Banjarmasin is designed to help Down syndrome children get facilities in the process of growth and development. In addition, this design can also be used to introduce Down syndrome to the general public. This design provides facilities in the form of basic therapy and training for down syndrome children, the therapeutic facilities provided consist of motor therapy, sensory therapy, and cognitive therapy. In solving the problems in this design, the Human-Centered design method is used so as to produce concepts that help design. The concept of educational games with the nuances of a zoo is also used as a reference to be able to provide good facilities and in accordance with the needs of Down syndrome children.